2016
DOI: 10.1177/1933719115612130
|View full text |Cite
|
Sign up to set email alerts
|

Swine Granulosa Cells Show Typical Endothelial Cell Characteristics

Abstract: Granulosa cells, which belong to the somatic compartment of the ovarian follicle, are actively involved as endocrine cells in follicle growth. Recently, it has been proposed that these cells are not terminally differentiated and possess multipotency. Therefore, we cultured swine granulosa cells in specific endothelial cell culture medium (EBM-2), and phenotypic and functional characteristics of endothelial cells were assessed. The collected data suggest that these endocrine cells can also behave as endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…Previous data describes the SKI expression in the embryo during the development of blood vessels—especially the aorta, and suggests that this gene is involved in the regulation of TGF-β signalling in arterial media during embryonic development (Doyle et al 2012). This information justifies the recent finding of Basini et al, who presented the evidence that GCs cultured in endothelial culture medium (EBM-2) gained functional and phenotypic characteristics of endothelial cells (Basini et al 2016).…”
Section: Discussionsupporting
confidence: 86%
“…Previous data describes the SKI expression in the embryo during the development of blood vessels—especially the aorta, and suggests that this gene is involved in the regulation of TGF-β signalling in arterial media during embryonic development (Doyle et al 2012). This information justifies the recent finding of Basini et al, who presented the evidence that GCs cultured in endothelial culture medium (EBM-2) gained functional and phenotypic characteristics of endothelial cells (Basini et al 2016).…”
Section: Discussionsupporting
confidence: 86%
“…It is well known that a co-operation between these two types of cells under gonadotrophic stimulation is possible. Granulosa cells like endocrine cells are actively involved in follicle growth and development (Basini et al, 2016), whereas theca cells are needed for folliculogenesis to synthesize androgen and provide cross-talk with granulosa cells and oocyte (Canipari et al, 2012). In the present study, mRNA encoding AQP5 during the early luteal phase (days 2-4) was the lowest in both granulosa and theca cells, which corresponds with the stage of formation of primordial follicles.…”
Section: Discussionmentioning
confidence: 75%
“…The establishment and continual remodelling of a complex vascular system influence the follicle development. According to Basini et al (2016) this angiogenic process is modulated by the biosynthetic activity of granulosa cells. In the follicles of all stages, this layer of cells remains avascular up to ovulation (Binelli and Murphy, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…CD105 null mice die by embryonic day 11.5 due to failure of endothelial remodeling [30], however, apart from playing an undoubtable role in vasculature development, endoglin is also involved in GCs function, since it is expressed by this type of cells [7,10,31]. It is generally accepted that follicle development is dependent on the establishment and continual remodeling of a complex vascular system, and was suggested that GCs may behave as endothelial cells and contribute to follicular angiogenesis [32]. Indeed, the study on porcine GCs conducted by Basini et al revealed that these cells express several endothelial markers, including CD105, and that this expression seems to be more pronounced in cells cultured in specific endothelial cell culture medium (EBM-2) [32].…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that follicle development is dependent on the establishment and continual remodeling of a complex vascular system, and was suggested that GCs may behave as endothelial cells and contribute to follicular angiogenesis [32]. Indeed, the study on porcine GCs conducted by Basini et al revealed that these cells express several endothelial markers, including CD105, and that this expression seems to be more pronounced in cells cultured in specific endothelial cell culture medium (EBM-2) [32]. We however observed gradual decrease of CD105 levels during porcine GCs in vitro culture, reaching the lowest level at 144 h, therefore it seems that in our culture conditions GCs lose their angiogenic potential.…”
Section: Discussionmentioning
confidence: 99%